2022
DOI: 10.3389/fcell.2022.896147
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine regulations in tissue-specific immunity: From mechanism to applications in tumor

Abstract: Immune responses in nonlymphoid tissues play a vital role in the maintenance of homeostasis. Lots of evidence supports that tissue-specific immune cells provide defense against tumor through the localization in different tissue throughout the body, and can be regulated by diverse factors. Accordingly, the distribution of nervous tissue is also tissue-specific which is essential in the growth of corresponding organs, and the occurrence and development of tumor. Although there have been many mature perspectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 175 publications
0
3
0
Order By: Relevance
“…In addition to the central nervous system, neuropils and neural factors within the peripheral region can function as immunomodulators in the development of cancer dyscrasia [204] . Cancer-mediated factors, such as Activin A and IL-6, can inhibit BMP action on muscle fibers and nerve terminals by expressing Noggin.…”
Section: Immune-neuron Axismentioning
confidence: 99%
“…In addition to the central nervous system, neuropils and neural factors within the peripheral region can function as immunomodulators in the development of cancer dyscrasia [204] . Cancer-mediated factors, such as Activin A and IL-6, can inhibit BMP action on muscle fibers and nerve terminals by expressing Noggin.…”
Section: Immune-neuron Axismentioning
confidence: 99%
“…The metabolism of tumors is often regulated by the neuroendocrine system, and abnormal neuroendocrine regulation may cause metabolic disorders (19). In addition, numerous studies have demonstrated that nerves' primary means of modulating tumor cells is through neuroendocrine modulation, which has also been linked to tumor start, development, and a worse prognosis (34)(35)(36). Studies show that catecholamine-induced neuroendocrine phenotype of GC cells accelerates GC progression (13).…”
Section: Discussionmentioning
confidence: 99%
“…The innervated microenvironment (IME) is a specialized micro-ecosystem that forms through communication between nerves and cancer cells via nerve-derived neurotransmitters or neuropeptides [22]. IMEs are categorized as intracranial or extracranial innervated niches.…”
mentioning
confidence: 99%